2007
DOI: 10.1029/2006jd008010
|View full text |Cite
|
Sign up to set email alerts
|

Trend of estimated actual evapotranspiration over China during 1960–2002

Abstract: [1] In this study, the water balance methodology introduced by Thornthwaite and Mather (1955) is modified to estimate monthly actual evapotranspiration for 686 stations over China during . The modification is done by replacing the Thornthwaite potential evapotranspiration estimation with the Penman-Monteith method. Temporal trend and spatial distribution of the estimated annual actual evapotranspiration during the past 43 years are analyzed. The results show that (1) the actual evapotranspiration had a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
174
2
5

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 212 publications
(196 citation statements)
references
References 38 publications
15
174
2
5
Order By: Relevance
“…It can be concluded that all five reanalysis data sets reasonably reproduce the spatial patterns of AE. Similar analysis of AE over China using the water balance methodology [Gao et al, 2007] has also demonstrated this result.…”
Section: 1002/2014jd023040supporting
confidence: 55%
See 4 more Smart Citations
“…It can be concluded that all five reanalysis data sets reasonably reproduce the spatial patterns of AE. Similar analysis of AE over China using the water balance methodology [Gao et al, 2007] has also demonstrated this result.…”
Section: 1002/2014jd023040supporting
confidence: 55%
“…In general, RE in North and Northeast China is nearly uniform, which ranges from 1 mm d À1 in the western part to nearly 3 mm d À1 near the Bohai Sea coast. The highest is NCEP-R1, which is much larger than the values given by Gao et al [2007]. However, the higher deviations in spatial variability and the amount of RE can be found in northwest China.…”
Section: Spatial and Temporal Variation Of Reanalysis Evaporationmentioning
confidence: 62%
See 3 more Smart Citations